Al3+-doping dependence on structural phase evolution in the LaCrO3 compound studied using atomistic simulation. (January 2021) - Silva, Romualdo S.; Otsuka, André M.; Ferreira, Nilson S.
Abstract: We report the atomistic simulation study of the Al 3+ -doping effects on the structural properties of LaCrO3 compound. We observed that Al 3+ -doping in the range of 0-80 wt% induced a decrease in the lattice parameters, unit cell volume, and Cr/Al-O and La-Cr/Al bond lengths. At the phase transition, around 60 wt% of Al 3+ -doping, and positive volume expansion was observed, which confirmed the orthorhombic ( Pnma ) to rhombohedral ( R-3c ) phase transition. The volume decompression amount was calculated to be about +0.50 Å 3 (+33.33%) per formula unit. The elastic constants of the unit cell expansion increased as Al 3+ -doping increased 80 wt%, and were estimated to be C11 =C33, C12 /C21 =C23 /C32, and C44 =C66 for the orthorhombic and rhombohedral phases, respectively. However, these constant values match to those of the rhombohedral structure for further Al 3+ -doping. Thus, we concluded that increasing substitution of Cr 3+ (0.615 Å) by Al 3+ (0.535 Å) in the LaCrO3 lattice induces a decrease of distortions at (Cr/Al)O6 octahedra, indicating that a reduction of the chemical pressure caused the structural phase transition. Highlights: Atomistic simulation is used to investigate the structural phase transition in LaCr1-x Alx O3 compounds. The lattice parameters and the bond lengths decrease with increasing Al-content; however, the distortion angle increases. Elastic constants tends to increase with increasing Al-content and reveal a discrepancy between 60 and 70 wt% of Al. The structural phase transition occurs effectively after 60 wt% of Al-content.